2018
DOI: 10.31219/osf.io/9zxqg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of digital elevation model resolution on the simulation of the snow cover evolution in the High Atlas

Abstract: The snow melt from the High Atlas represents a crucial water resource for crop irrigation in the semi-arid regions of Morocco. Recent studies have used assimilation of snow cover area (SCA) data from high resolution optical sensors to compute the snow water equivalent (SWE) and snow melt in other mountain regions. These techniques require large model ensembles and therefore a challenge is to determine the adequate model resolution, which yields accurate results with reasonable computation time. Here we study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Mountainous areas also experience substantial precipitation during summer, due to small-scale convection (Born et al, 2008). As a consequence, vegetation outside the lower elevation valleys is sparse, essentially lim- ited to bare soil, grass and occasional shrubs (Baba et al, 2019). Snowfall is common between November and March above 1500 m elevation, and it is frequent to observe snow cover persisting for several months above 2500 m (Marchane et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Mountainous areas also experience substantial precipitation during summer, due to small-scale convection (Born et al, 2008). As a consequence, vegetation outside the lower elevation valleys is sparse, essentially lim- ited to bare soil, grass and occasional shrubs (Baba et al, 2019). Snowfall is common between November and March above 1500 m elevation, and it is frequent to observe snow cover persisting for several months above 2500 m (Marchane et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Within a topographical class, observations are affected by (1) natural variability, (2) retrieval errors and (3) classification errors. In particular, DEM errors and resolution have a strong impact in satellite retrievals via shadows and subgrid topography (Baba et al, 2019;Davaze et al, 2018), leading to about ±10% errors in broadband albedo for MODIS data (Dumont et al, 2012). Moreover, S2 data are particularly affected by the three sources, since the retrieval DEM (SRTM90) in the MAJA processor is too coarse to capture the topographic variability at the scale of the pixels (10-20 m) and because the classification is done to an even much coarser scale (IGN250).…”
Section: On the Relevance Of The Comparison In The Semi-distributed Fmentioning
confidence: 99%
“…The 90 m Shuttle Radar Topography Mission (SRTM) digital elevation model was used after resampling it to 200 m spatial resolution by using cubic interpolation. The choice of the spatial resolution is based on a previous study in the Rheraya catchment [36], where we analyzed the trade-off between spatial resolution and the computation time. This study suggested that a distributed snow model with a grid coarser than 250 m is not able to capture the high spatial variability in the snow cover patterns due to the importance of the incoming solar radiation in the snowpack energy budget.…”
Section: Topography and Land Covermentioning
confidence: 99%
“…We chose the 2008-2009 snow season for which we dispose of an accurate time series of high resolution SCA maps from Formosat-2 data [8]. [36]. These intervals were chosen following the recommendations of Froidurot et al [48].…”
Section: Snowpack Modelmentioning
confidence: 99%